A Death of a Man Due to Strong Acid Trauma at a Rice Field, a Homicide or Suicide ? - Trisnadi, Setyo (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2016)
In general highly corrosive acids or bases injury can occur due to deliberate or unintentional, such as workplace-related accidence, vocational negligence, unintentional child corrosive poisonings. Acids are considered to be corrosive when it has a high concentration, are irritants at moderate concentrations, and stimulant at low concentrations. This is a report of a strong acid poisioning case of a 60 year-old- man found dead in the middle of a rice field in Demak in September 2015. The victim was one of the farmers protesting the illegal dredging project. At the crime scene, a hoe and a bottle made of “plastic” (used fertilizer container, classified as moderate acid) lying beside the deceased, giving an impression that he commited suicide by consuming the liquid. External examination revealed: burn marks are red brown or black, dry and hard on the eyelids, nostrils, lips, tongue, neck and chest. The results of the examination showed: 1. Mucosal irritation, with a bright red and brownish red, accompanied by ulceration. It was also found irritation in tongue, larynx and edemous glottis and esophagus. 2. Pseudomembranous inflammation of the trachea and bronchi which resulted in superficial epithelial damage and necrosis affect submucosal layer. 3. Brain edema due to anoxia. The forensic examination confirms that the cause of death was homicide.